Next-generation care pathways for allergic rhinitis and asthma multimorbidity: a model for multimorbid non-communicable diseases—Meeting Report (Part 1) - Bousquet, Jean; Pham-Thi, Nhân; Bedbrook, Anna; Agache, Ioana; Annesi-Maesano, Isabella; Ansotegui, Ignacio; Anto, Josep M.; Bachert, Claus; Benveniste, Samuel; Bewick, Mike; Billo, Nils; Bosnic-Anticevich, Sinthia; et al. (Journal of Thoracic Disease, 2019)
In all societies, the burden and cost of allergic and chronic respiratory diseases are increasing rapidly. Most economies are struggling to deliver modern health care effectively. There is a need to support the transformation of the health care system for integrated care with organizational health literacy. MASK (Mobile Airways Sentinel NetworK) (1), a new development of the ARIA (Allergic Rhinitis and its Impact on Asthma) initiative, and POLLAR (Impact of Air POLLution on Asthma and Rhinitis, EIT Health) (2), in collaboration with professional and patient organizations in the field of allergy and airway diseases, are proposing real-life integrated care pathways (ICPs) (3)-centred around the patient with rhinitis and using mHealth monitoring of environmental exposure (4).